2016
DOI: 10.1038/gim.2015.29
|View full text |Cite|
|
Sign up to set email alerts
|

Treacher Collins syndrome: a clinical and molecular study based on a large series of patients

Abstract: Purpose: Treacher Collins/Franceschetti syndrome (TCS; OMIM 154500) is a disorder of craniofacial development belonging to the heterogeneous group of mandibulofacial dysostoses. TCS is classically characterized by bilateral mandibular and malar hypoplasia, downward-slanting palpebral fissures, and microtia. To date, three genes have been identified in TCS:,TCOF1, POLR1D, and POLR1C. Methods:We report a clinical and extensive molecular study, including TCOF1, POLR1D, POLR1C, and EFTUD2 genes, in a series of 146… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
126
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(141 citation statements)
references
References 24 publications
10
126
1
4
Order By: Relevance
“…Given the strong interaction between POLR1D (RPAC2) and POLR1C (RPAC1) in yeast, POLR1C , which also encodes a subunit of RNA polymerase I and III (Figure ), was sequenced leading to the identification of mutations in both POLR1C alleles in three affected individuals. In all cases, one mutant allele was inherited from each phenotypically unaffected parent, confirming autosomal recessive inheritance in a very small subset of TCS patients (OMIM248390) …”
Section: Treacher Collins Syndromesupporting
confidence: 56%
See 1 more Smart Citation
“…Given the strong interaction between POLR1D (RPAC2) and POLR1C (RPAC1) in yeast, POLR1C , which also encodes a subunit of RNA polymerase I and III (Figure ), was sequenced leading to the identification of mutations in both POLR1C alleles in three affected individuals. In all cases, one mutant allele was inherited from each phenotypically unaffected parent, confirming autosomal recessive inheritance in a very small subset of TCS patients (OMIM248390) …”
Section: Treacher Collins Syndromesupporting
confidence: 56%
“…In all cases, one mutant allele was inherited from each phenotypically unaffected parent, confirming autosomal recessive inheritance in a very small subset of TCS patients (OMIM248390). 37,39 The Biochemical Basis of TCS: The Role of Treacle in Ribosome Biogenesis TCOF1 encodes the low complexity, nucleolar phosphoprotein Treacle which contains putative nuclear export and nuclear import signals at the N-and and C-termini, respectively, together with a central repeat domain which is subject to a high degree of phosphorylation by casein kinase 2. 22,23,40 Immunofluorescence studies indicated that Treacle exhibits nucleolar localization dependent upon C-terminal motifs, 41,42 and subsequently, Treacle was shown to colocalize with UBF, one of two transcription factors required for accurate transcription of human ribosomal RNA genes by RNA polymerase I (PolI) ( Figure 3).…”
Section: Focus Articlementioning
confidence: 99%
“…Previous to this report, the literature includes 69 individuals (64 kindreds) with mutations of EFTUD2 (NM_004247.3), excluding individuals with cytogenetically visible chromosomal aberrations [Lines et al., ; Gordon et al., ; Need et al., ; Bernier et al., ; Luquetti et al., ; Voigt et al., ; Lehalle et al., ; Gandomi et al., ; Smigiel et al., ; Sarkar et al., ; Vincent et al., ]. Here, we summarize all published affected individuals and present genotypic and phenotypic data from a further 38 affected individuals belonging to 30 kindreds (Supp.…”
Section: Variantsmentioning
confidence: 99%
“…Biallelic mutations in POLR3A have been very recently described as genetic cause underlying Wiedemann–Rautenstrauch syndrome (Paolacci et al, ). Although the phenotypes belonging to the mandibulofacial dysostosis/Treacher Collins syndrome spectrum share some features with HSS including micrognathia, high palatal vault, and malar hypoplasia, the affected patients usually show external ear abnormalities and lower eyelid colobomas (Vincent et al, ) and these spectrum phenotypes are clinically well distinguishable from HSS. Oculodentodigital dysplasia also shares several clinical characteristics with HSS, such as microphthalmia, small nose, hypotrichosis, and dental anomalies.…”
Section: Clinical Features Of Hallermann–streiff Syndromementioning
confidence: 99%